HUMANISTIC LITERACY DESIGN MODEL BASED ON DIALOGICAL PEDAGOGY TO DEVELOP CRITICAL THINKING AND SOCIAL EMPATHY OF MADRASAH IBTIDAIYAH STUDENTS - Didah Nurhamidah; Lutfi Syauki Faznur (PD PGMI se Indonesia, 2025)
This study aims to examine a humanistic literacy design model based on dialogical pedagogy in developing the critical thinking skills and social empathy of Madrasah Ibtidaiyah students. The background of this study stems from the low levels of literacy achievement and critical thinking among elementary school students, which are still dominated by teacher-centered learning approaches and have not optimally integrated humanistic, dialogical, and social dimensions in the learning process. This study employs a descriptive qualitative approach, with data collected through classroom observations, in-depth interviews, and learning documentation conducted in several Madrasah Ibtidaiyah in Bogor Regency. Dialogical pedagogy is understood as a learning approach that places dialogue, social interaction, and the negotiation of meaning at the core of the learning process. Its implementation is strengthened through interpersonal communication strategies, including teacher role modeling and credibility (ethos), empathy and emotional warmth (pathos), as well as logical reasoning and argumentation (logos). The findings indicate that the application of a humanistic literacy model based on dialogical pedagogy encourages active student participation, enhances reflective expression of ideas, and fosters social sensitivity and empathy in learning interactions. The learning syntax of orientation, exploration, elaboration, application, evaluation, and generalization creates an inclusive, dialogical, and reflective classroom atmosphere. This study concludes that the model effectively integrates the development of critical thinking and social empathy in a balanced manner and is aligned with the spirit of the Independent Curriculum, making it relevant for shaping critical, empathetic, communicative, and humanistic Madrasah Ibtidaiyah students in the context of 21st-century education.